Prediction of mediastinal lymph node metastasis in adenocarcinoma of the esophagogastric junction - Nienhüser, Henrik; Schmidt, Thomas (Journal of thoracic disease, 2019)
The optimal surgical management of adenocarcinoma of the esophagogastric junction (AEG) is challenging and complex. While Siewert type I tumors are treated according to the algorithm of esophageal cancer the optimal approach for Siewert II/III tumors is still under debate (1). In particular, the best operative approach and the extend of lymph node dissection were investigated in several studies without clear consensus (2,3).